2000
DOI: 10.1093/jexbot/51.348.1221
|View full text |Cite
|
Sign up to set email alerts
|

Protein modification by Amadori and Maillard reactions during seed storage: roles of sugar hydrolysis and lipid peroxidation

Abstract: The non-enzymatic modifications of proteins through Amadori and Maillard reactions play an important role in the loss of seed viability during storage. In the present study, the contribution of sugar hydrolysis and lipid peroxidation to Amadori and Maillard reactions, and to seed deterioration was investigated in mung-bean (Vigna radiata Wilczek). The contents of glucose and lipid peroxidation products in seed axes increased significantly during storage. The accumulation of Amadori products in seed axes was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(27 citation statements)
references
References 15 publications
2
22
1
2
Order By: Relevance
“…The products of both sugar hydrolysis and lipid peroxidation can initiate non-enzymatic protein and DNA degradation via Amadori and Maillard reactions. Despite reports of the inhibition of enzymatic and auto-oxidation of lipids at the seed MCs used in this study [13.2, 11.4, and 10.2% (fresh mass basis) for P. sativum , L. pratensis , and C. scoparius , respectively; Murthy and Sun, 2000], malondialdehyde and 4-hydroxynonenal were detected in aged P. sativum seeds, indicating that lipid peroxidation did occur and may have contributed to Maillard reactions.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The products of both sugar hydrolysis and lipid peroxidation can initiate non-enzymatic protein and DNA degradation via Amadori and Maillard reactions. Despite reports of the inhibition of enzymatic and auto-oxidation of lipids at the seed MCs used in this study [13.2, 11.4, and 10.2% (fresh mass basis) for P. sativum , L. pratensis , and C. scoparius , respectively; Murthy and Sun, 2000], malondialdehyde and 4-hydroxynonenal were detected in aged P. sativum seeds, indicating that lipid peroxidation did occur and may have contributed to Maillard reactions.…”
Section: Discussioncontrasting
confidence: 76%
“…Under such storage conditions, metabolic activity is minimal due to the low molecular mobility of cell cytoplasm. One mechanism of seed ageing is via Maillard reactions, which occur following a non-enzymatic attack on amino groups of proteins and nucleic acid–protein complexes by reducing sugars or aldehydes (Murthy and Sun, 2000). This forms advanced glycosylation end-products, which are found in both naturally and artificially aged seed tissues, and increase during storage at all MCs and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Non-enzymatic browning may result from Maillard and Amadori reactions starting from a condensation reaction between reducing sugars and amino groups. These reactions are known to produce carbonyl intermediates which react with neighboring amino groups [36]. Protein glycation is a process in which reducing sugars interact with primary amines on the side chains of Lysine and Arginine, resulting in a chemical sequence of reactions known as “Amadori rearrangement” which leads to the formation of Amadori modified proteins (AMPs).…”
Section: Resultsmentioning
confidence: 99%
“…McDonald (1999) suggested that the secondary of lipid peroxidation, such as malondialdehyde, was likely to be involved in the breakdown of proteins and nucleic acids through the Amadori and Maillard reactions. However, the involvement of lipid peroxidation in seed degradation during storage is still subject to debate (Narayana Murthy and Sun, 2000).…”
Section: Resumen Efecto Del Envejecimiento Acelerado Sobre La Composimentioning
confidence: 99%